To design with time manifesto - Silva, Cidália Ferreira (2018)
Project Lab2PT – Landscapes, Heritage and Territory laboratory – AUR/04509 with the financial support from FCT/MCTES through national funds (PIDDAC) and co-financing from the European Regional Development Fund (FEDER) POCI-01-0145-FEDER-007528, whithin the framework of the new partnership agreement PT2020 throught COMPETE 2020 – Competitiveness and Internationalization Operational Program (POCI).